Might makes right: war-related payments in Bosnia and Herzegovina - Hronešová, J (Routledge, 2016)
This article explores the patterns of distribution of material reparations (compensation) for victims and veterans in post-1995 Bosnia and Herzegovina. Drawing on bottom-up approaches to reparative justice and critical peacebuilding, it explains the existing material reparation schemes in Bosnia as outcomes of the post-war transition and interests of the main transitional actors. It first explores the different approaches to war-related compensation for victim and veteran groups and then demonstrates that veterans have formed powerful pressure groups, drawing on extensive political and economic resources. Their organizations have been receiving socioeconomic support in exchange for electoral endorsement and public political support. As victims are fragmented ethno-nationally, by categories, and also lack capacities, their means to leverage the authorities for change are limited, even when matched with NGO and international support. This paper argues that unless material reparation is distributed in a transparent and consistent manner, it may create additional social cleavages and tensions.